Floristic stability and stratification of ecosystems in the Central Basin: towards a resilience model in Central Africa - Evariste Loke Lobanga et al. (International Journal of Scientific Research and Innovative Studies, 2026)
Faced with growing anthropogenic pressures in the Central Basin of the Congo, identifying resilient forest groups is imperative to ensure the sustainability of the carbon sink. This study analyses the structure and diversity of 60 permanent plots spread across three contrasting sites: Isangi, Uma and Mambasa. We adopted a refined vertical reading by distinguishing the understorey (diameter at breast height, DBH ≤ 60 cm) from the canopy (DBH > 60 cm). Three dominant assemblages, anchored by Scorodophloeus zenkeri, Staudtia kamerunensis and Cynometra alexandri, were identified. These groups exhibit high alpha diversity (Shannon H' index), inverted J-shaped diameter structures and marked stratification, signs of strong ecological stability. Our results demonstrate that the synergy between floristic diversity and architectural complexity maximises above-ground biomass (AGB). These data provide a robust scientific basis for establishing resilient model forests in the Congo Basin. Keywords: Congo Basin, floristic diversity, ecological resilience, forest stratification Received Date: February 22, 2025 Accepted Date: March 14, 2026 Published Date: April 02, 2026 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/586